‫المراجعة ‬‫الخارجية‬ ‫كمدخل‬ ‫لتحسين‬ ‫جودة‬ ‫الملعلومة‬ ‫المالية‬ ‫‪‬‬‫دراسة‬ ‫ميدانية‬ ‫لعينة‬ ‫من‬ م‫حافظي‬ ‫الحسابات‬ ‫و‬ ‫الخبراء‬ ‫المحاسبين‬ ‫لولايت‬ ‫سوق‬ ‫أهراس‬ ‫و‬ ‫عنابة‬ ‫‪‬‬ - كوثر ‫قوامسية‬‫‬ (My University, 2018)
ing the quality of financial information through the standards and principles that govern them through following a set of steps to do it, Since the financial information is the solid base in an institution and the different decisions are build upon, it was necessary to have external auditing as it highly helps on guaranteeing the production of an authentic neutral and independent financial information, Therefore there has been questionnaire to analyze this topic, this questionnaire has been distributed among a sample of thirty (30) person in order to test the views of some employees (book keepers and accounting experts), After collecting and analyzing information using the program SPSS, the results of the questionnaire find that the external auditing helps in achieving a set of standards and provisions which achieve the quality of the financial information, Moreover it finds that book keepers and accounting experts have a role in proving the legitimacy of accountings and financial lists and make them reflect the real status of the institution and enhance the trust for its users, This study concluded that the external auditing has an effective role in improving the quality of financial information.